Peripheral Arterial Disease in Type 2 Diabetes Is Associated with an Increase in Fibrinogen Levels - Qin-Fen Chen; Dan Cao; Ting-Ting Ye; Hui-Hui Deng; Hong Zhu (International Journal of Endocrinology)
Background. The present study is undertaken to investigate the fibrinogen levels in type 2 diabetes mellitus (T2DM) and its relation to peripheral artery disease (PAD) based on a more accurate and applied noninvasive measurements of duplex ultrasonography. Methods. We performed a cross-sectional study including 1096 T2DM patients (474 males and 622 females). The odds ratios (ORs) and 95% confidence intervals (CIs) were presented to show the association between PAD and fibrinogen in the subjects divided by fibrinogen levels quarterly. Furthermore, the univariate and multiple logistic analyses were performed to explore the correlation between PAD and fibrinogen levels, individual components in the cross-sectional study. Results. Finally, 887 (80.9%) T2DM patients meet the diagnostic criteria of PAD and these patients had considerably higher serum fibrinogen concentration than non-PAD group (P<0.001). Multiple logistic analyses revealed that higher fibrinogen quartiles were positively related with the development of PAD in the adjusted model. After adjusting for known confounding parameters, the ORs for PAD were 1.993 (95% CI: 1.322-3.005, P<0.001), 2.469 (95% CI: 1.591-3.831, P<0.001), and 2.942 (95% CI, 1.838-4.711, P<0.001) for Q2, Q3, and Q4, respectively (all P values <0.05). Conclusions. Our results suggest that serum fibrinogen concentration can be considered as an independent risk factor for PAD in T2DM patients.